PENGEMBANGAN WISATA ALAM DESA LUMPANGI KABUPATEN HULU SUNGAI SELATAN - Herman Herman; Abdi Fithria; Khairun Nisa (Jurnal Sylva Scienteae, 2022)
The purpose of this research is to review the development of Natural Tourism in Lumpangi Village Hulu Sungai Selatan Regency, reviewing the biophysical identification of Lumpangi Village, inventory of natural attractions, community perception, and determine Development Strategy. The method used to determine community respondents using purposive sampling methodology and visitor respondents using accidental sampling. The results showed the identification of flora amounted to 33 flora and the number of fauna as much as 25 fauna physical state of Lumpangi Village field is hills and slopes. While the inventory of natural attractions there are rivers, mountains, forests, diversity of fauna, and diversity of flora. Public perception of the development of nature tourism in Bukit Langara has a positive impact, namely increasing the economy. Determining the right development strategy judging by SWOT analysis by evaluation using IFAS and EFAS matrices with determination based on the position in the quadrant of the matrix. Based on IFAS and EFAS Results the number of strengths and opportunities (S+O=3.85+3.85 = 7.7; number of strengths and threats (S+T) = 3.85 + (-2.40) = 1.45; number of weaknesses and threats (W+T) = (-2,40)+(-2.40) = -4.80 and number of weaknesses and odds (W+O) = (-2.40)+(3.85) = 1.45. The value of the internal factor is 1.45 as the value of X, while the value of external factors is also 1.45 as the value of Y, which concluded that the natural tourism of Langara Hill is positive.Tujuan Penelitian ini adalah untuk mengkaji pengembangan Wisata Alam Desa Lumpangi Kabupaten Hulu Sungai Selatan, Mengkaji Identifikasi Biofisik Desa Lumpangi, Inventarisasi atraksi alam, persepsi masyarakat dan menentukan Strategi Pengembangan. Metode yang di gunakan untuk menentukan responden masyarakat menggunakan metode purposive sampling dan responden pengunjung menggunakan accidental sampling. Hasil Penelitian menunjukkan identifikasi flora berjumlah sebanyak 33 flora dan  jumlah fauna sebanyak 25 fauna keadaan fisik lapangan Desa Lumpangi merupakan perbukitan dan lereng-lereng, sedangkan inventarisasi atraksi alam terdapat sungai, gunung, hutan, keanekaragaman fauna, dan keanekaragaman flora. Persepsi masyarakat terhadap pengembangan wisata alam Bukit Langara memberikan dampak positif yaitu peningkatan perekonomian. Strategi pengembangan yang tepat dilihat dari analisis SWOT dengan evaluasi menggunakan matriks IFAS dan EFAS dengan penentuan strategi berdasarkan posisi pada kuadran matriks. Berdasarkan Hasil IFAS dan EFAS jumlah kekuatan dan peluang (S+O=3,85+3,85 = 7,7 ; jumlah kekuatan dan ancaman (S+T) = 3,85 + (-2,40) = 1,45; jumlah kelemahan dan ancaman (W+T = (-2,40)+(-2,40) = -4,80 dan jumlah kelemahan dan peluang (W+O) = (-2,40)+(3,85) = 1,45. Nilai dari Faktor internal 1,45 sebagai nilai X, sedangkan nilai faktor eksternal juga 1,45 sebagai nilai Y maka dapat di simpulkan bahwa wisata alam Bukit Langara bersifat positif.